Sistem Pengendali Banjir Dan Genangan Di Kawasan Jalan Satria Kota Pekanbaru - Handayani, Yohanna Lilis; amad, Ali; Sujatmoko, Bambang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Satria street is located at the flood plain of Sail River in Pekanbaru city which is oftenly flooded by high intensity rainfall during the rainy season. Due to its low elevation, water tends to flow and form puddles on the street area. This study aims to overcome the aforementioned problem by performing drainage normalization simulation at Satria Street using HEC-CRAS 4.1.0 software. The normalization was conducted by increasing both width and depth of the drainage ditch from the existing dimensions of 50 cm x 70 cm to 80 cm x 100 cm, and by changing the drainage slope at Satria Street. The design-flow rate an rainfall intensity was computed using rational method and mononobe method, respectively. The analysis result show that the flood problem can be coped by modifying the slope and dimensions of the drainage ditch.Keywords: flood, drainase, Hec-Cras